Efektivitas Celup Puting Menggunakan Ekstrak Buah Mengkudu (Morinda Citrifolia) terhadap Hasil Uji California Mastitis Test (CMT) - Theresia Ika Purwantiningsih; Yustina Yuni Suranindyah; Widodo Hadisaputro (Universitas Sebelas Maret (UNS), 2017)
The purpose of this study was to determine the effectiveness of nipple dip with mengkudu extact (Morinda citrifolia) on CMT test result. Mengkudu contains anti-bacterial substances, consisting of acubin, L. asperuloside, alizarin and some antraquinon substances that have been shown to show strength against pathogenic bacteria. This study used four Friesian Holstein (FH) cows which are known for sub-clinical mastitis and nipple dyeing solution from mature noni fruit. Nipple FH dipped using 30% concentration of noni fruit extract. After dyed, a Californian mastitis test (CMT) was performed. Based on the stastistic analysis of T-Test used, extract of noni fruit significantly (p <0,01) can inhibit bacteria cause mastitis. Noni fruit extract is able to inhibit the spread of bacteria that cause mastitis, thus lowering the risk of mastitis.